Lion and spotted hyena distributions within a buffer area of the Serengeti-Mara ecosystem - Stanslaus B. Mwampeta; Clay M. Wilton; Imani J. Mkasanga; Lusato M. Masinde; Peter S. Ranke; Eivin Røskaft; Robert Fyumagwa; Jerrold L. Belant (Scientific Reports, 2021)
Abstract Most large carnivore populations are declining due to anthropogenic activities including direct persecution, prey depletion, habitat loss and degradation. protected areas (PAs) can help maintain viable large carnivore populations; however, anthropogenic activities occurring near and within PA borders or edges can reduce their effectiveness. We investigated the influence of edge effects on abundance of lions (Panthera leo) and spotted hyenas (Crocuta crocuta) in Maswa Game Reserve (MGR), a part of the Serengeti ecosystem in northern Tanzania. We conducted repeated call-ins to attract and enumerate lions and hyenas at 20 stations in MGR during June–July 2017. We used N-mixture models to estimate hyena and lion abundance in relation to land cover and distance from the south-western MGR borders which are adjacent to villages. We found lowest lion and hyena abundances by the south-western border, with abundance of both species increasing toward the eastern border adjacent to Serengeti National Park. Lions were uniformly distributed among land covers whereas hyenas were more abundant in woodlands. We suggest that reduced lion and hyena abundance near human settlements was in response to depleted prey, due to human actions. We recommend ecologically compatible land uses and effective border patrols to mitigate these adverse effects.